EFFECT OF SENAM SEHAT ANAK INDONESIA IN MAXIMUM OXYGEN CONSUMPTION IN CHILDHOOD OBESITY - Arniari, Gek Yun; Isma AP, Rahmi; Setiawati, Erna; Nency, Yetty Movieta (DIPONEGORO MEDICAL JOURNAL (JURNAL KEDOKTERAN DIPONEGORO), 2020)
Background: Obesity is one of the causal factors of chronic diseases such as heart disease, diabetes, hypertension, asthma, arthritis, and cancer. The change in lifestyle and lack of physical activity in children increase the incidence of obesity, accompanied by a decrease in physical fitness. One of the parameters that can be used to determine the level of physical fitness is the maximum oxygen consumption (VO2max). VO2max in children can be increased through aerobic physical exercise, such as Senam Sehat Anak Indonesia (SSAI). SSAI combines aerobic movements and joyful music in order to motivate children to be more excited in gymnastics. Methods: An Experimental study with the pre-post test design among 23 samples who fulfill the inclusion and exclusion criteria. The exercises were administered twice a week for six weeks. VO2max data were measured before and after the exercise in the first week and week 12. Data of VO2max were analyzed using the data normality test with Shapiro-Wilk, then continued with Wilcoxon test to determine the difference of VO2max. Results: There is significant difference of VO2max between before and after SSAI (p < 0.05). Conclusion: There is an increase in the maximum oxygen volume (VO2max) after the SSAI exercise in childhood obesity.